Encryption algorithms for biometric data protectionRecibido: julio 23 de 2023 | Revisado: setiembre 20 de 2023 | Aceptado: octubre - Chavez-Ferrel, Marvin (2024)
The objective of this review was to examine thedifferent biometric data encryption techniques oralgorithms used in authentication for informationsecurity. Consequently, the PRISMA methodologywas used to select articles in different databases duringthe period between 2019 and 2023. The databasesused were SCOPUS, SCIELO and GOOGLEACADEMICO, where when applying the proposedinclusion and exclusion criteria, they were considered13 articles for this research. In this way, it was possibleto notice the need to apply encryption algorithms asa form of attack prevention and aimed at meetingthe objectives of information security, the most usedbeing AES (Advanced Encryption Standard) andencryption chaotic.